2021
DOI: 10.1053/j.gastro.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of SARS-CoV-2 Infection in Patients With Chronic Liver Disease and Cirrhosis: A National COVID Cohort Collaborative Study

Abstract: Background and Aims In chronic liver disease (CLD) patients with or without cirrhosis, existing studies on the outcomes with SARS-CoV-2 infection have limited generalizability. We used the National COVID Cohort Collaborative (N3C), a harmonized electronic health record (EHR) dataset of 6.4 million, to describe SARS-CoV-2 outcomes in patients with CLD and cirrhosis. Methods We identified all CLD patients with or without cirrhosis who had SARS-CoV-2 testing in the N3C Dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
111
2
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 40 publications
(58 reference statements)
2
111
2
8
Order By: Relevance
“…When compared with SARS-COV-2 patients with non-cirrhotic CLD, they report an adjusted 30-day mortality HR of 3.31. 14 This risk is higher than adjusted risks for hospitalised patients identified in our systematic review, likely due to the high proportion of non-hospitalised patients in this study and the difference in risk of hospitalisation between groups (CLD 22.9% vs cirrhosis 50.1%). 14 Observational studies within our meta-analysis include predominantly patients who were hospitalised or presented to hospitals.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…When compared with SARS-COV-2 patients with non-cirrhotic CLD, they report an adjusted 30-day mortality HR of 3.31. 14 This risk is higher than adjusted risks for hospitalised patients identified in our systematic review, likely due to the high proportion of non-hospitalised patients in this study and the difference in risk of hospitalisation between groups (CLD 22.9% vs cirrhosis 50.1%). 14 Observational studies within our meta-analysis include predominantly patients who were hospitalised or presented to hospitals.…”
Section: Discussioncontrasting
confidence: 52%
“…Ge et al have reported data from the N3C Consortium in the USA which uses electronic healthcare record data to identify patients who underwent SARS-CoV-2 testing or had related symptoms. 14 In total, 8941 patients with cirrhosis and COVID-19 were identified. When compared with SARS-COV-2 patients with non-cirrhotic CLD, they report an adjusted 30-day mortality HR of 3.31.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although these studies have been limited by issues of selection bias, generalizability, and imperfect control groups, they have been critical in establishing cirrhosis as a major risk factor for poor outcomes from COVID-19. The study by Ge and colleagues 4 confirms the main findings of these studies using a larger and nationally representative patient cohort with more recent follow-up data.…”
supporting
confidence: 74%
“…3 In this issue of Gastroenterology, Ge and colleagues 4 conduct a retrospective cohort study to evaluate the outcomes of patients with cirrhosis and COVID-19 using electronic health record data from the National COVID Cohort Collaborative Data Enclave, or N3C. 4 The N3C is a novel, centralized, curated, national repository of harmonized electronic health record data from clinical sites across the United States, with the National Center for Advancing Translational Sciences at the National Institutes of Health serving as data steward. It was formed in response to the need for rapid accrual of large-scale data on COVID-19.…”
mentioning
confidence: 99%
See 1 more Smart Citation